Essential nursing guidelines: clinical skills and procedures - Hassan, Hamidah; Mat, Samsiah; Panduragan, Santhna Letchmi; Nurumal, Mohd. Said; Karim, Jalina (Penerbit Universiti Malaysia Sabah, 2021)
This book is the first to be developed in Malaysia with the collaborations of nurses from the Ministry of Higher Education Malaysia, Malaysian Ministry of Health and Malaysian Nursing Board. The initial effort took place in 2010 until it was revised in 2019. The collaboration involved was nurses from various fields of nursing. They were nursing lecturers, nursing supervisors, nurse specialists and nurse consultants and a team from the Malaysian Nursing Board. The main purpose to develop this book was to make it a reference and reading material for the nursing students. We also hope that this book can be a lectern of clinical learning material and standardize all the nursing procedures and skills in the country. Several new procedures have been included in this edition to keep pace with the latest changes in nursing knowledge and those on the market. The selection of procedures and skills was based on the sights and references from experienced nursing individuals and the latest clinical nursing textbooks. This book contains 17 units and 136 basic procedures or skills as tools to deliver patient care. The followings are the main modules in which there are only pertinent procedures included; Fundamental of Nursing, Vital Signs, Personal Hygiene, Bed Making, Moving and Positioning, Maintaining Airway and Oxygenation, Oral and Enthral Nutrition, Specimen, Bowel and Elimination, Comfort Measures, Medication, Intravenous, Wound Care, Bandages, Intraoperative Procedures, Special Procedures and Care After Death. Lastly, we also hope that this book will continue to be the source of opportunity for the nurses in Malaysia to write, enduring to improve this book to the second edition and following current needs.